2009
DOI: 10.1080/00207450903192860
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Profile of Memory Compromise Among HIV-1-Infected Individuals

Abstract: WMS-III indices discriminated HIV+ participants from normal comparisons. Inability to find differences between HIV+ and depressive and LD groups reflects the isolation of the subcortical effect to the HIV+ group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…below the seronegative group, in agreement with other studies [78][79][80][81][82][83][84][85][86][87][88][89][90], and again, it was noteworthy that co-infected patients in the early/asymptomatic stage of HIV-1 infection presented a significantly poorer performance in more complex tasks, suggesting additional limitations in initiating a systematic search of information in short-term/working memory [91]. Memory abilities are important for independent and successful management of activities of daily living [80,87], therefore, co-infected patients would be at higher risk of dependence on others in everyday functioning [87].…”
Section: Plos Onesupporting
confidence: 92%
“…below the seronegative group, in agreement with other studies [78][79][80][81][82][83][84][85][86][87][88][89][90], and again, it was noteworthy that co-infected patients in the early/asymptomatic stage of HIV-1 infection presented a significantly poorer performance in more complex tasks, suggesting additional limitations in initiating a systematic search of information in short-term/working memory [91]. Memory abilities are important for independent and successful management of activities of daily living [80,87], therefore, co-infected patients would be at higher risk of dependence on others in everyday functioning [87].…”
Section: Plos Onesupporting
confidence: 92%
“…Five studies provided enough information to calculate effect sizes, which ranged from 0.45 to 1.12 [32, 33, 3537]. Despite impaired recall, individuals infected with HIV often demonstrated intact recognition abilities [3133]. There is also evidence of HIV-associated deficits in visual memory [24, 30, 31, 33, 34] with similar effect sizes ranging from 0.64 to 1.03 [24, 31, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Despite impaired recall, individuals infected with HIV often demonstrated intact recognition abilities [3133]. There is also evidence of HIV-associated deficits in visual memory [24, 30, 31, 33, 34] with similar effect sizes ranging from 0.64 to 1.03 [24, 31, 33]. Two additional studies finding HIV-related memory impairment created a composite score that included performance on both visual and verbal memory tasks, and so the specific contributions of each domain is unclear [30, 34].…”
Section: Resultsmentioning
confidence: 99%
“…HAND symptoms result from neurodegeneration caused by the infiltration of the virus into the brain, and is characterized by a number of cognitive deficits [31]: one study found that cognitively asymptomatic HIV-positive individuals displayed abnormal visual spatial attention processing compared to HIV-negative controls [32], another found that HIV-positive individuals showed significant deficits in verbal working memory storage and processing [33], and another group characterized immediate, delayed (auditory/visual), and working memory deficits in HIV-positive males compared to controls, which they attributed to subcortical gray and white matter damage due to HIV infection [34]. …”
Section: Hiv-associated Neurocognitive Disorders (Hand)mentioning
confidence: 99%